Development of Teaching Materials with Thunkable Applications to Support Blended Learning in Tennis - Septian Raibowo; Sugihartono, Dian Pujianto; Sugihartono, Tono; Andes Permadi (UNIB Press, 2023)
This research aims for the future to facilitate Physical Education Study Program students with various teaching materials to support blended learning. Learning. Especially teaching materials that help students' cognitive learning. Because it is known that nowadays and with the sophistication of technology, learning can be done anywhere and at any time by students. In fact, this also makes the college learning process easier because having teaching materials as a learning resource for students can help learning in lectures become more effective and efficient. Because having additional teaching materials as a student learning resource will enrich student knowledge. Specifically for this research, teaching materials will be developed using the Thunkable Tennis Court application. In the future, there will be gradual development for other types of teaching materials and other materials as well. As is known, the physical education study program is closely related to learning movement. Learning to move yourself is also divided into several stages which include cognitive, associative and automatic stages. The cognitive stage is the beginning and basis that influences success at other stages. Because it is necessary for an educator to provide effective and efficient learning at this stage and provide enrichment of knowledge to students by using up-to-date teaching materials in accordance with current developments. The method to achieve this goal will be Research and Development from year to year. What is certain is that the Research and Development stage begins with needs analysis, product development, validation, testing and publication.